Investigation of DRA and non-DRA in locust compound eye on the phototactic response of locust - Liu, Qihang; Liu, Minghao; Yang, Bo; Zhang, Pingchuan; Cui, Jinxin; Zhao, Huiyuan (International Journal of Agricultural and Biological Engineering, 2024)
New approaches are required to prevent the plagues of locusts that threaten crop security in many areas of the world. One such approach is to exploit the phototactic response of locusts, enabling their aggregation and effective removal from agricultural sites. This study examined the effect of the dorsal rim area (DRA) of the locust compound eye on the phototactic response of locusts to spectral light. Locusts with intact DRA showed increased phototactic responses to blue, green or orange light but decreased responses to UV and violet light, whereas locusts with blacked-out DRA (non-DRA vision) showed the strongest phototactic responses to orange followed by violet light. The combined results revealed that phototactic push-pull effect triggered by responses of DRA versus non-DRA vision was strongest in response to violet light. Compound vision in the locust is the result of the synergism between DRA versus non-DRA vision, causing a push-pull phototactic effect that is most stimulated by exposure to violet light, with light intensity enhancing this effect. These results provide theoretical support for the induction of phototaxis and polarotaxis in response to light in locusts, which could be useful for the development of light-based control systems in the field. Keywords: Locusta migratoria, DRA vision, non-DRA vision, phototactic response, function effectDOI: 10.25165/j.ijabe.20241705.8556Citation: Liu Q H, Liu M H, Yang B, Zhang P C, Cui J X, Zhao H Y. Investigation of DRA and non-DRA in locust compound eye on the phototactic response of locust. Int J Agric & Biol Eng, 2024; 17(5): 81-87.